Longitudinal Decline in Lung Function Measurements among Saskatchewan Grain Workers - Punam Pahwa; Ambikaipakan Senthilselvan; Helen H McDuffie; James A Dosman (Canadian Respiratory Journal)
OBJECTIVE: To evaluate the relationship between the long term effects of grain dust and decline in lung function among grain elevator workers in Saskatchewan, studied over a 15-year period.